The use of hematology method and blood endoparasite observation for determining catfish (Clarias gariepinus) health in fishery Mangkubumen, Boyolali - INTAN ESTETIKA ALAMANDA; NOOR SOESANTI HANDAJANI; AGUNG BUDIHARJO (Biodiversitas Journal of Biological Diversity, 2007)
This research aims to find out the health condition of catfish (Clarias gariepinus) based on hematology and to find out the blood endoparasite type of catfish (Clarias gariepinus) bred in Mangkubumen Boyolali. The sample collection of catfish in this research was conducted in Mangkubumen, Boyolali. The catfish becoming the sample had following criteria: 3 month old, 100-150 gr weight, and 20-25 cm long. The sample of catfish was taked from 5 pools, it was taken 10 fishes from each pool. The hematological parameter measurement including erythrocyte number , leukocyte number, hemoglobin content, hematocrit value, and the preparation of blood smear preparation was conducted in UNS central laboratory. The hematological parameter data of catfish sample obtained was compared with the hematological parameter of the healthy catfish. The smear preparation was used for observing the endoparasite existence on sample blood of catfish. The result of research shows the hematocrit value of 19.3 – 23.3 %, the erythrocyte number of 1.4 – 2.5 x 106 cells/mm3, the hemoglobin content of 6.46 – 7.93 Hb/100ml below that of the healthy catfish. The leukocyte number 650 – 750 x 103 cells/mm3 above that of the healthy catfish. Entire catfish indicate the sickness due to the parasite infection. Endoparasit found in the blood of catfish are: Trypanosoma sp, Sanguinicola sp, Haemogregarina sp.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Catfish, hematology, blood endoparasite.